Study on the targets for PZT thin films fabrication process using Rf reactive sputtering / Sukreen Hana Herman and Abdul Karimi Halim - Herman, Sukreen Hana; Halim, Abdul Karimi (2006)
The purpose of this research is to conduct a thorough study on the targets for PZT thin films fabrication process. The targets play a.very important role on determining the films composition and quality, thus by conducting a thorough study on the targets, will improve the process efficiency and also the films quality. PZT thin films are widely used as the material for electronics devices, especially for Ferroelectric Random Access Memory (FeRAM). Thus research and studies on PZT has been conducted extensively. However, since lead that contained in PZT is hazardous to health and environment, studies has been conducted to develop lead-free materials to replace PZT, but still PZT has the best characteristics that suits the electronics devices. To overcome the lead problem in PZT, research has been done to reduce the lead usage during PZT fabrication process. From this study, it is confirmed that PbO₂ target is an efficient oxygen supply during PZT fabrication process. By using PbO₂ target, lead amount during the process can be reduced, and also oxygen gas amount can be reduced that will results in a simpler and faster process.